Climate change litigation: a handbook - Kahl, Wolfgang; Weller, Marc-Philippe (Beck, 2021)
Climate Change Litigation This handbook investigates and discusses the respective issues arising in the current discourse on climate protection from different legal perspectives (including international law, European law and national public and civil law). In particular, it addresses the issue of “climate protection by courts”. It gives an overview about important jurisdictions in the field of Climate Change Litigation, including inter alia the US, Canada, Australia, UK, France, The Netherlands, Italy, Brazil and Germany. The book aims to pave the way for research in the field of climate change litigation, which up to this point has surprisingly remained untrodden ground in Germany or Europe. Furthermore, it is guaranteed to provide an overview of the latest news in cases and progress in the field of climate change litigation.
Keywords: Handbuch; Aufsatzsammlung; Umweltrecht; Prozessrecht; Auswirkung; Klimaänderung